Cover crops for early season weed suppression in corn - Smith, Malynda Marie (Kansas State University, 2021)
Integrated weed management is becoming more important to prevent herbicide-resistant weeds from reducing corn yield. This study examined the influence various combinations of cover crop species, termination timing, and N rate had on early-season weed suppression and corn yield at Manhattan and Ottawa in 2019 and 2020. Fall cover crops of triticale (x Triticosecale Wittm.), pea (Pisum sativum L.), and triticale + pea (mixed) were sown in November 2018 and 2019, with the exception of pea sown in spring 2019. Two cover crop termination timings, three weeks before (3WBP) or at corn planting (AP), were subplot factors. The sub-subplot factor was N broadcast applied as urea at rates of 100 or 168 kg N ha⁻¹ within two weeks after planting in both years. Cover crops were terminated and no-cover treatments were treated with glyphosate and 2,4-D. Cover crop biomass was collected at termination and weed density was counted regularly from 3WBP through the POST herbicide application of atrazine, glyphosate, and mesotrione at three weeks after planting. Weed density and biomass were collected in August 2020 to quantify control by the POST application. Cover crop biomass production ranged from 2,500 to 7,600 kg ha⁻¹ in the mixed and triticale treatments when terminated AP in both years. Weed density was influenced by cover crop species and termination time at Manhattan with reductions of 51 to 59% by using cover crops compared to no cover and 44% when terminated AP compared to 3WBP. There was no reduction in weed density at Ottawa by delay in termination timing, likely due to little cover crop biomass production. Yield was variable between the two locations. Delay in termination timing and the triticale cover crop reduced yield at Manhattan in both years by 14 to 19%. At Ottawa, a 15% increase in yield was observed when termination timing was delayed from 3WBP to AP, and yield increased by 11% with increased fertilizer applied from 100 to 168 kg N ha⁻¹, regardless of cover crop type. Results indicated that cover crops generated varying results over different regions, soil types, and field management histories, as was exemplified by the locations of this study. Data from this study suggest that using a cover crop species that has high biomass production and corn fertilization with a minimum of 168 kg N ha⁻¹ will result in greater weed suppression and less corn yield loss than cover crop treatments fertilized with 100 kg N ha⁻¹. .
Keywords: Cover crops; Corn; Weed management; Integrated weed management